Kształtowanie strategii firmy - Pogodina, W.W. (Shaping the corporate strategy, 2006)
The paper presents a systemic approach to strategy. This allows orderly development. Consideration of interdependence between goals, development potential and external conditions is the key to success. In dynamic conditions interactions between these elements are continuous.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 247-250